Calculation of thermodynamic parameters of BBC crystals xafs theory - Hung, Nguyen Van; Thai, Vu Kim; Duc, Nguyen Ba (VNU Journal of Science: Natural Sciences and Technology; Vol 16 No 2, 2000)
Abstract